Strategies in Power Relations in a Fictional Work: A Foucauldian Analysis - Gartika Rahmasari; Iis Kurnia Nurhayati (TEKNOSASTIK, 2019)
In a family, power relations can be seen in a father-child relationship, where the father has the authority to control the life of the child and the child must approve the father's decision. Not only the father, however, the son might also have different objective that he wants to achieve. Here both parties will usually try to keep pursuing their own objectives. In other words, both parties will look for strategies of how to win their objective in the power relation by acting certain ways. Hence, strategy can be used as the means to obtain victory (Foucault, 2002). The purpose of this paper is to analyze power relations that occurred in a family in a fictional work, namely Family Matters novel by Rohinton Mistry, particularly between Nariman Vakeel and his father, Marzi Vakeel. Nariman’s objective is to acquire his father’s approval for his desire to marry his girlfriend, Lucy Braganza, who is a Catholic. This is the opposite of Marzi’s belief, that his family should marry a Parsi. Power relations and strategies used between Nariman and his father were examined using the theory of power relations from Michel Foucault. The findings show that each character implements different strategies in imposing power and confronting each other. As for Nariman, his strategies include persuading his father, and when this does not work, he started to show a clear insubordination every time. On the other hand, Marzi’s strategies include writing a letter to newspaper to let other people know his opposition to interfaith marriage, objecting Lucy’s presents in his house by rejecting Nariman’s suggestion to invite Lucy over for dinner, and being patience in confronting Nariman’s insubordination for eleven years. During these years, Marzi never utilized violence. In the end, Marzi succeeded in achieving his objective to make Nariman marry a Parsi woman when Nariman was finally tired of confronting his father, and let his father choose a Parsi woman. Nariman ended up having an arranged marriage.Keywords: Family, Foucault, power relation, strategies